Oral Presentations Abstracts: ETHICAL ISSUES IN THE ROMANIAN PHARMACEUTICAL SYSTEM IN THE CONTEXT OF COVID-19 PANDEMIC - RUS, Lucia Maria; HEGHEȘ, Simona Codruța; CACOVEAN, Adela; HUI, Ligia Ancuța; UIFĂLEAN, Alina; IUGA, Cristina Adela (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 COVID-19 infection is a disease caused by the new type Coronaviruses family strain, SARS-CoV-2. It was first identified in China’s Wuhan City in December 2019. On March 11, 2020, the World Health Organization officially declared the public health emergency with COVID-19 a pandemic. As in the other affected countries, Romania’s health care professionals are on the front line. Among them, community pharmacy and clinical pharmacy teams are facing special ethical situations related to issues as: the provision of protective equipment, sudden medicines price rises, a general increased need in pharmaceutical services of the population concerned about COVID-19, a possible shortage of drugs due to the cessation of their import, ensuring on-going provision of pharmaceutical services in the case of significant volumes of staff absences.